Physical Obstacles To The Success Of The Sports Professionalism System In Algerian Football Sport (field Study On The Clubs Of The First And Second Professional League Mobilis) - تريش لحسن (sports creativity, 2025)
Professionalism in Algerian football is one of the most important and vital issues on the sports scene, directly impacting the game's development. The existing professional system is a primary reason for the decline in performance, contrary to initial expectations. Therefore, Algeria is attempting to establish clear criteria for the financing of sports clubs. Before the professional era, clubs were funded through contributions from the state, local authorities, and economic institutions. State funding was channeled through national economic institutions, which served as the financial backbone for clubs, covering expenses such as player and staff salaries. These institutions fulfilled their role as guarantors until the onset of the economic crisis. To address the deteriorating situation of football clubs, the majority are constantly struggling with limited financial resources. They often find themselves unable to pay player salaries, let alone acquire new players to strengthen the squad. Furthermore, they struggle to cover the costs of sports activities, transportation, and equipment for the entire season. Given the financial circumstances of professional sports clubs in Algeria, we conducted this study on the financial obstacles hindering the success of the professional system in Algerian football.